MANOTA: a promising bifunctional chelating agent for copper-64 immunoPET. Issue 42 (1st September 2017) - Moreau, M.; Poty, S.; Vrigneaud, J.-M.; Walker, P.; Guillemin, M.; Raguin, O.; Oudot, A.; Bernhard, C.; Goze, C.; Boschetti, F.; Collin, B.; Brunotte, F.; et al.
Abstract : A comparison of four bifunctional chelating agents showed superior behaviour of a new NOTA derivative for 64 Cu labelling of antibody fragments. Abstract : Improved bifunctional chelating agents (BFC) are required for copper-64 radiolabelling of monoclonal antibodies (mAbs) under mild conditions to yield stable, target-specific imaging agents. Four different bifunctional chelating agents (BFC) were evaluated for Fab (Fragment antigen binding) conjugation and radiolabelling with copper-64. Two DOTA- (1, 4, 7, 10-tetraazacyclododecane-1, 4, 7, 10-tetraacetic acid) and two NOTA- (1, 4, 7-triazacyclononane-1, 4, 7-triacetic acid) derivatives bearing a p -benzyl-isothiocyanate group were conjugated to Fab-trastuzumab – which targets the HER2/ neu receptor – and the average number of chelators attached ranged from 2.4 to 4.3 macrocycles per Fab. Labelling of the immunoconjugate with copper-64 was achieved in high radiochemical yields after 45 min at 37 °C, and the radiochemical purity of each 64 Cu-BFC-Fab-trastuzumab reached 97% after purification. The affinity of each 64 Cu-BFC-Fab-trastuzumab ranged between 10 and 50 nM as evaluated by in vitro saturation assays using the HCC1954 breast cancer cell line. PET-MR imaging and biodistribution studies were performed in mice bearing breast cancer BT-474 xenografts. BT-474 tumours were clearly visualized on PET images at 4 and 24 hours post-injection. The tumour uptake of 64 Cu-BFC-Fab-trastuzumab reached 8.9 to 12.8% ID g −1 24 hours post-injection and significant differences in non-specific liver uptake were observed depending on the BFC conjugated, the lowest being observed with MANOTA. These results show that MANOTA is a valuable tool for copper-64 radiolabelling.